Evaluation of Drug Regimens Used for the Prophylaxis of Thromboembolic Events in a Referral Cancer Center in North of Iran - Saeed Dehkia; Bizhan Kouchaki; Ghasem Janbabaei; Ramin Shekarriz; Shahram Ala; Ebrahim Salehifar (Research Center for Rational Use of Drugs (RCRUD), 2017)
Background: Venous thromboembolism (VTE) is a major cause of mortality among cancer patients. The aim of this study was to evaluate drug regimens used for the prophylaxis of thromboembolic events in cancer patients. Methods: A retrospective study was conducted using medical records of patients hospitalized from March 2012 to March 2014 at Cancer Division of A tertiary university-affiliated hospital in North of Iran. The risk factors of patients regarding need of venous thromboembolic (VTE) prophylaxis were recognized and dosage and duration of thromboembolic prophylactic agents were evaluated according to the National Comprehensive Cancer Network (NCCN) 2012 guidelines. Statistical analysis was performed using SPSS v.23. Results: Of a total of 1160 medical records, VTE prophylaxis regimens of 186 patients were evaluated. In 18(13.1%) and 15(10.9%) of patients, administrations were compatible with NCCN guidelines with respect to the "type of drug" and "dosage", respectively. Only in 7(5.1%) of patients administrations were compatible with respect to the "duration of thromboembolic prophylaxis regimen". Forty patients (21.7%) had relative contraindication for thromboembolic prophylaxis and 7(3.8%) patients had absolute contraindication. In 32(80%) of 40 patients with relative contraindications and only in 1(14.3%) of 7 patients with absolute contraindications, physicians' orders were compatible with NCCN guidelines. Conclusion: The rate of concordance of the VTE prophylaxis with recommendations provided by NCCN is very poor. This study emphasizes need of a multidisciplinary action to improve the VTE prophylaxis in cancer patients.